Relative elevation of the Rio Bermejo with respect to its floodplain - Repasch, Marisa N; Scheingross, Joel S; Cook, Kristen L; Sachse, Dirk; Dosch, Sophia; Orfeo, Oscar (In: Repasch, MN et al. (2023): River water chemistry, channel morphometrics, and river incision data for the Rio Bermejo, Argentina [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.959938, 2023)
Relative elevation data was extracted from the map of residual topography over 25-40 km swaths extending from the Rio Bermejo channel centerline. We quantified the superelevation and incision of the Rio Bermejo relative to the surrounding topography by making a residual elevation map (sensu Cohen et al. (2015, doi:10.1130/2015.1212(16); McGlue et al. (2016, doi:10.2110/jsr.2016.82)). We created a series of 1 km wide swaths set perpendicular to the Rio Bermejo flow direction and extracted the minimum elevation of the active Rio Bermejo channel within each swath using the TanDEM-X DEM. Variability in DEM values for water surfaces created ~2-4 m noise in elevation values of the active channel which we smoothed by fitting a 4th order polynomial to the extracted active channel elevations to estimate the downstream change in elevation. We subtracted the polynomial fit from the DEM to yield a DEM that was de-trended from the Rio Bermejo channel slope, with values representing the local relief between the active channel and the surrounding terrain.
Keywords: Argentina; channel migration rates; fluvial geomorphology; Foreland basin; river morphometrics; water chemistry